(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf de jcf HOdfG ef Cf JCJi Ydi eSQM eG ajgG ceG aYdfG ajeG JbOe ef gPg GdcJH YedJ cJGHi gPG hSejJg GdcGed s
(3BNQgG (B:s
(3hfMf PGcQhf ai GdLRA GdKGdK ef Ydhe GdMjhGf WQbkG jchf HgG TQM eG JbOe dfG ai GdcJH ef QehR ai CehQ GdMjhGf Je GdLRA GdChd ef GdcGed HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs